Analisis semiotika Roland Barthes pada Film Tarung Sarung (Interpretasi budaya Laki-Laki Berani) - Ibnu Hajar; Kamaluddin Tajibu; Andi Fauziah Astrid (Departement of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2022)
This study aims to examine the cultural message of brave men in the film Tarung Sarong with the objectives, 1) to find out the meaning of denotations, connotations, and myths contained in the film Tarung Sarong 2) to know the cultural message of brave men contained in the film Tarung Sarong This research uses qualitative methods with semiotic analysis in order to make it easier to analyze the symbols/signs in the film. Data collection was carried out by watching the film first and observing the dialogue and images in the Tarung Sarong film, or other data related to the research object and having relevant and factual data. The results of the research show that in the film Tarung Sarong is a picture of a man who has a courageous attitude and responsibility in solving a problem he faces in the land of Bugis, Makassar. This film contains 12 cultural messages for brave men in the film Tarung Sarong, namely, mobs are not problem solving, men must dare to take responsibility, have a chivalrous spirit, side with the truth, uphold siri', be responsible for their own problems, do not deify money, social spirit, mutual help, learning to obey iklas, the firmness of the Bugis Makassar people in solving problems, and the attitude of resignation. The implications of this research are expected to be able to contribute to competent parties in the field of semiotic analysis and increase knowledge about cultural messages in the film